Expression of Markers of Innate Immune Response in Indigenous Pig of Northeast India in Comparison to Crossbred and Hampshire - Hadem, K L H; Puro, K; Bhatacharjee, U; Sen, A; Samir, S; Ghatak, G; Sanjukta, R; Shakuntala, Shakuntala; Rajkhowa, D. J (Indian Journal of Hill Farming, 2017)
The function of innate immune system is to act as first line of defense against infectious/pathogenic challenge to the animals. A correlation between pathogen responses with genetic variation in immune response in pigs has been reported. Here we present the study on expression of innate immune response markers (IL-6, IL-12, INF-Î³, IL-1Î², TNF-Î± and c - reactive protein) in indigenous pig along with crossbred and Hampshire. The results suggest there exists difference in the expression pattern of markers in various breeds. This information may serve as an indicator for rational design or evaluation of immune response of porcine.